Intraventricular methotrexate as part of primary therapy for children with infant and/or metastatic medulloblastoma: Feasibility, acute toxicity and evidence for efficacy. Issue 17 (November 2015) - Pompe, Raisa S.; von Bueren, André O.; Mynarek, Martin; von Hoff, Katja; Friedrich, Carsten; Kwiecien, Robert; Treulieb, Wiebke; Lindow, Christine; Deinlein, Frank; Fleischhack, Gudrun; Kuehl, Joachim; Rutkowski, Stefan
Highlights: Infections were the majority of IVAD associated complications. Toxicity seems to be rare and usually mild (6%) apart of one therapy associated death. The total dose of i.ventr. MTX was determined as an independent risk-factor for survival. Abstract: Background: To assess feasibility, acute toxicity, and efficacy of intraventricular methotrexate administered as part of the primary therapy in medulloblastoma. Methods: From 2001 to 2007, 240 patients <22 years from 61 treatment centres were registered. Patients received 2–3 cycles of intraventricular methotrexate with systemic chemotherapy in three different treatment arms of the prospective multicentre trial HIT2000 (150 children >4 years with metastatic, 59 <4 years with non-metastatic, 31 <4 years with metastatic medulloblastoma). Results: 211 patients received an intraventricular access device with a subcutaneous reservoir for the application of chemotherapy. Reservoir-associated complications were documented in 57 (27%) patients, mostly due to infection ( n  = 32) and reservoir malfunction ( n  = 19), requiring removal in 39 (18%) patients. Acute neurotoxicity likely associated with intraventricular MTX was observed in 9/202 documented patients. Toxicity was usually mild, apart from one therapy-associated death due to toxic oedema followed by seizures. Of 519 treatment cycles including intraventricular methotrexate, 226 (43%) were reduced or omitted, most frequently due to the absence of an intraventricular device. Survival rates were higher in patients receiving ⩾75% of the scheduled intraventricular methotrexate dose compared to those receiving <75% in both univariate and multivariate models (event-free survival (EFS), 61.5 versus 46.2%, p  = 0.004; OS, 75.5% versus 60.4%, p  = 0.015; hazard ratio: EFS 1.723, p  = 0.016; OS 1.648, p  = 0.051). Conclusion: Intraventricular methotrexate therapy was feasible and mostly well tolerated. Infections were the most frequent complication. A higher cumulative dose of intraventricular methotrexate was associated with better survival. Further evaluation of efficacy and late effects is warranted.